Enhancing Mufradat Memorization Through Word Square Learning Media: A Study of Class VII Students at MTs Muhammadiyah Pinrang - Nur Madinah; Nur Fadilah Fadilah Amin; Abd. Rahman (Al-Muyassar: Journal of Arabic Education, 2025)
This study explores the application of Word Square learning media to enhance the memorization of Arabic mufradat (vocabulary) among seventh-grade students at MTs Muhammadiyah Pinrang. The research addresses the challenge of low vocabulary retention, a critical issue in Arabic language learning, and aims to determine whether the interactive, game-based Word Square method can enhance student engagement and memorization.A Classroom Action Research (CAR) design was employed, conducted in two cycles. Data were collected through observations, pre- and post-tests, and documentation, and analyzed using both qualitative and quantitative methods. In the first cycle, while student engagement increased, only a modest improvement in vocabulary retention was observed. Adjustments were made in the second cycle, including simplifying the puzzles and encouraging collaborative learning, which led to a significant increase in student performance.The results showed that Word Square is an effective tool for improving vocabulary retention, with most students achieving "good" levels of recall by the end of the second cycle. The interactive and collaborative nature of the activity played a crucial role in fostering a more engaging and supportive learning environment.The study concludes that Word Square can be a valuable alternative to traditional vocabulary teaching methods, offering practical insights for educators seeking to enhance language instruction. The findings suggest further research on long-term retention and the use of Word Square for other language skills could broaden the tool's applicability.Â Keywords: Word Square, Arabic Mufradat, Vocabulary Retention, Collaborative Learning.